The efficiency of sensory systems in postural control of children with and without hearing or visual impairments - Hamed Zarei; Ali Asghar Norasteh; Lauren J. Lieberman; Michael W. Ertel; Ali Brian (PLoS ONE, 2025)
Limited evidence exists on the efficiency of the sensory systems of children with sensory impairment. The purpose of this study was to examine the sensory systems involved in postural control of male children with hearing (HI) or visual impairments (VI) compared to those without HI or VI. Participants aged 9–13 years old (N = 45, Mage = 11.43, SD = 1.5) were placed within one of three equally stratified purposive groups (HI, VI, comparison children). Postural control was measured using a Kistler force plate (with stabilometric parameters: mean velocity in the anterior-posterior (AP) and medial-lateral (ML), standard deviation (SD) velocity in the AP and ML directions, and sway area) applying four different sensory conditions; condition A: standing on two legs on a stable surface with the eyes open and without any sensory interference (assessment of postural control); condition B: standing on two legs on a stable surface with eyes closed and hyper-extension of the head (perturbation of vestibular and visual system: assessment of proprioceptive system); condition C: standing on two legs on an unstable surface with hyper-extension of the head (perturbation of vestibular and proprioception system: assessment of visual system); condition D: standing on two feet on an unstable surface and eyes closed (perturbation of proprioception and visual system: assessment of vestibular system). The results indicated that in the assessment of postural control condition, comparison children had smaller center of pressure (COP) parameters than children with VI and HI (p = 0.001). Also, children with HI had smaller COP parameters compared to VI (p = 0.001). In the assessment of proprioceptive system condition, comparison children had greater COP parameters than children with HI and VI (p = 0.001). In conclusion, comparison children had better postural control than children with VI and HI; and children with HI had better postural control than children with VI. The proprioceptive system of children with VI and HI performed better than comparison children in maintaining postural control. Consequently, children with VI, HI, and comparison children depend on the proprioceptive system more than other sensory systems to maintain postural control.